English into Korean Simultaneous Interpretation of Academy Awards Ceremony Through Open Captions on TV - Lee, Taehyung (Meta, 2011)
This article used video-editing software to explore the temporal aspects of the live coverage of the Academy Awards Ceremonies, which employed simultaneous interpretation (SI) and open Korean captions at the same time. The results showed that the Korean captions appeared 7.24 seconds after the beginning of the original sentences and remained on the screen 7.52 after the end of original. These figures were statistically longer than other live coverage of the same events with SI alone and other TV programs carrying live captions. It was also found that relatively short original sentences were omitted in SI and the long EVS (ear-voice-span) also left the sentences that followed uninterpreted. In spite of the long time lag, questionnaires indicated that viewers preferred SI through open captions to SI alone presumably because they could listen to the original voices of entertainers without being disturbed by the voice-over of SI.